Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2025)
Table of Content: • Multi-Dimensional Strategic Model to Enhance Institutional Performance Under Digital Transformation: An Applied Framework in the Saudi Context Ms. Mona Jeza Almutairi , Mr. Hassan Khidhr Alhallafi, Mr. Almotasim Khalil Alabbas • The Role of Strategic Management in Achieving Administrative Creativity at Prince Sattam University in Al-Kharj Governorate from the Perspective of Administrative Employees Ms. Kholoud Ghaleb Mubarak Al-Dosari • Digital Transformation in Government Services: Enhancing Efficiency, Accessibility, and Citizen Experience: A Case Study of The United Arab Emirates (UAE) Dr. Khawla Mossa Abdulla AlHaiyas • Evaluating the Transformations of the Bura Biosphere Reserve in Yemen: A reading of the Environmental, Social, and Economic Context Asst-Prof. Bardees Taher Al-Okab • The Financial Management of Stock in the Path of Allah in Achieving Economic Stability and Security Asst-Prof. Hazem Mahmoud Alwadi • Liquidity and Leverage Effects on Sudatel’s Financial Performance (2015–2024) Dr. Najla Fateh Elrhman Elgadi • The Contribution of Soft leadership Skills on Organizational Change: A Study on Sudanese Insurance Companies Co-Prof. Mohammed Mukhtar Ibrahim , Asst-Prof. Adam Yagoub Abker